APPLICATION OF SMART GRID PRINCIPLES IN WEAPON STABILIZERS FOR OPTIMIZING POWER DISTRIBUTION - TKACHUK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The modernization of light armored vehicles increasingly relies on advanced weapon stabilization systems that ensure high accuracy of fire under dynamic conditions. However, the growing complexity and precision of such systems are directly associated with a substantial increase in energy consumption, creating significant challenges for onboard power distribution. Traditional power supply architectures, typically based on diesel generators and batteries, often fail to ensure stable operation during peak loads, such as rapid turret rotation or the compensation of weapon recoil. These limitations lead to voltage drops, reduced efficiency, and accelerated wear of power components. Furthermore, operational experience in modern conflicts has highlighted the problem of maintaining long-term functionality of weapon stabilizers in silent watch mode, where engines remain switched off to reduce acoustic and thermal signatures. In such conditions, conventional systems rapidly deplete batteries, compromising combat readiness. This paper proposes the application of Smart Grid principles to the energy management of weapon stabilization systems in light armored vehicles. The proposed architecture integrates bidirectional DC/DC converters, high-density lithium-ion batteries, and supercapacitors, coupled with regenerative technologies that capture and reuse kinetic energy during braking and stabilization maneuvers. Intelligent energy management algorithms dynamically prioritize power distribution, ensuring critical subsystems receive uninterrupted supply even during extreme operational scenarios. Modeling conducted in MATLAB/Simulink demonstrated that the Smart Grid-based approach reduced peak energy consumption by 20–25%, increased the overall efficiency of the power supply system from 78% to 91%, and extended autonomous operation time by approximately 25%. These results confirm the potential of Smart Grid integration to enhance not only energy efficiency but also the reliability and survivability of light armored platforms on the modern battlefield. The findings emphasize that Smart Grid-based solutions represent a promising direction for the development of next-generation weapon stabilization systems. Future research should focus on the implementation of digital twins and artificial intelligence algorithms for predictive energy consumption analysis and early fault detection, thus further increasing system efficiency, resilience, and combat readiness.